Bonsoir pouriez vous m'aider svp
1/a)5x(x² +3); b)-2x(a+5); c) (y-3)x6; d)-4(2-b)
e)7(-z-4); f)-2(-c+1)


2/a) 6(3x²-4; b) -3(7+2a) c) 5(-y+1);
d) (1-b)x4; e) z(z+5); f) 2c(c-1)

2
f) +2c-2
2.a ) 18x² - 24
Tu veux qu'on fasse quoi exactement ?
2.b) -21 - 6a
que vous developper les expression

Réponses

  • Utilisateur Brainly
2014-03-02T22:07:39+01:00
1) 
a)
A= 5x(x²+3)
A= 5x³ + 15x
b)
B=-2x(a+5)
B= -2xa -10x
c)
C= (y-3)x6 
C= 6y -18
d) 
D= -4(2-b)
D= -8 + 4b
e)
E= 7(-z-4)
E= -7z -28
f)
F= -2(-c+1)
F= 2c -2
2)
a)
A= 6(3x²-4)
A= 18x² - 24
b)
B= -3(7+2a)
B= -21 -6a
c)
C= 5(-y+1)
C= -5y +5
d)
D= (1-b)x4
D= 4 -4b
e)
E= z(z+5)
E= z² +5z
f) 
F= 2c(c-1)
F= 2c² -2c
2014-03-03T00:04:34+01:00
1) 
a) 5x (x² + 3)
= 5x³ + 15x

b) -2x (a + 5)
= -2xa -10x

c) (y - 3) x 6 
= 6y -18

d) -4(2-b)
-8 + 4b

e) 7 (-z - 4)
= -7z  - 28

f) -2(-c + 1)
= 2c - 2

2)a) 6 (3x² - 4)
= 18x² - 24

b) -3 (7 + 2a)
= -21 - 6a

c) 5 (-y + 1)
= -5y + 5

d) (1 - b) x 4
= 4 - 4b

e) z (z + 5)
= z² + 5z

f) 2c (c - 1)
= 2c² - 2c